[4 + 2]-Cycloaddition an 1,1-Bis(3-indolyl)ethene als 3-Vinylindoläquivalente mit gekreuzt konjugiertem 6π System - Ludwig Pfeuffer; Ulf Pindur (CHIMIA)
1,1-Bis(3-indolyl)ethenes (3) react as 4π electron systems with dienophiles (e.g. acrylic acid methyl ester, tetracyanoethylene, benzyne, maleic anhydride, and 4-phenyl-1,2,4-triazoline-3,5-dione) to give cycloadducts of Diels-Alder type. The results demonstrate, that [4 + 2]-cycloaddition with vinylindole equivalents represents a strategy be realized for deriving selectively functionalized carbazole derivatives.